Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

=
Given the functions f(x) = x2 + 4
and
h(x)= x-2, find (f - h)(x)


Sagot :

Step-by-step explanation:

f(x) = x² + 4

h(x) = x - 2

Find (f-h)(x)

= f(x) - h(x)

= (x² + 4) - (x - 2)

= x² - x + (4 - (-2))

= x² - x + 6

(f - h)(x) = x² - x + 6